The Zé Lensky Dataset: A Brazilian Portuguese Twitter Corpus for Russo-Ukraine War Stance and Sentiment Analysis - Purim, Andreis G. M.; Kuškēvics, Kārlis (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2025: Anais do XVI Simpósio Brasileiro de Tecnologia da Informação e da Linguagem HumanaDO - 10.5753/stil.2025.37858, 2025)
This paper presents a work-in-progress corpus of over 200,000 Brazilian Portuguese tweets related to the Russia-Ukraine war, collected between 2022 and 2025. The dataset includes metadata and annotations for stance and irony, with particular attention to partisan and culturally specific expressions such as “zé lensky”, which we hypothesize indicate processes of sociolinguistic enregisterment in partisan speech. This resource enables further exploration of political discourse in Brazilian social media and supports future studies on narrative dynamics, user behavior, and informal political language. The dataset is available on GitHub.